Behavioural activation written self-help to improve mood, wellbeing and quality of life in people with dementia supported by informal carers (PROMOTE): a study protocol for a single-arm feasibility study. Issue 1 (December 2016) - Farrand, Paul; Woodford, Joanne; Llewellyn, David; Anderson, Martin; Venkatasubramanian, Shanker; Ukoumunne, Obioha; Adlam, Anna; Dickens, Chris
Abstract Background Increases in life expectancy have resulted in a global rise in dementia prevalence. Dementia is associated with poor wellbeing, low quality of life and increased incidence of mental health difficulties such as low mood or depression. However, currently, there is limited access to evidence-based psychological interventions for people with dementia experiencing low mood and poor wellbeing. Behavioural activation-based self-help, supported by informal carers and guided by mental health professionals, may represent an effective and acceptable solution. Methods/design The present study is a phase II (feasibility) single-arm trial informed by the Medical Research Council complex interventions research methods framework. Up to 50 dementia participant/informal carer dyads will be recruited from a variety of settings including primary care, dementia-specific health settings and community outreach. People living with dementia will receive behavioural activation-based self-help and be supported by their informal carer who has received training in the skills required to support the self-help approach. In turn, during the use of the intervention, the informal carer will be guided by mental health professionals to help them work through the materials and problem solve any difficulties. Consistent with the objectives of feasibility studies, outcomes relating to recruitment from different settings, employment of different recruitment methods, attrition, data collection procedures, clinical delivery and acceptability of the intervention will be examined. Clinical outcomes for people with dementia (symptoms of depression and quality of life) and informal carers (symptoms of depression and anxiety, carer burden and quality of life) will be measured pre-treatment and at 3 months post-treatment allocation. Discussion This study will examine the feasibility and acceptability of a novel behavioural activation-based self-help intervention designed to promote wellbeing and improve low mood in people living with dementia, alongside methodological and procedural uncertainties associated with research-related procedures. As determined by pre-specified progression criteria, if research procedures and the new intervention demonstrate feasibility and acceptability, results will then be used to inform the design of a pilot randomised controlled trial (RCT) to specifically examine remaining methodological uncertainties associated with recruitment into a randomised controlled design. Trial registration Current Controlled TrialsISRCTN42017211